Analysis of putative resistance gene loci in UK field populations of Haemonchus contortus after 6 years of macrocyclic lactone use. Issue 10 (September 2016) - Laing, Roz; Maitland, Kirsty; Lecová, Lenka; Skuce, Philip J.; Tait, Andy; Devaney, Eileen
Graphical abstract: Highlights: Field populations of Haemonchus contortus were collected from UK sheep farms. Farms with 6 years of macrocyclic lactone (ML) use or avoidance were compared. Parasites were genotyped at microsatellite loci and putative ML resistance loci. No evidence of ML selection was detected at Hc-lgc-37, Hc-glc-5, Hc-avr-14 or Hc-dyf-7. These loci are unlikely to be suitable for diagnostic marker development in the UK. Abstract: Sheep farmers in the UK rely on strategic anthelmintic use to treat and control gastrointestinal roundworms in their flocks. However, resistance to these drugs is now widespread and threatens the sustainability of sheep production. The mechanisms underlying resistance to the most commonly used class, the macrocyclic lactones, are not known and sensitive diagnostic tools based on molecular markers are not currently available. This prohibits accurate surveillance of resistance or assessment of strategies aimed at controlling its spread. In this study, we examined four UK field populations of Haemonchus contortus, differing in macrocyclic lactone treatment history, for evidence of selection at 'candidate gene' loci identified as determining macrocyclic lactone resistance in previously published research. Individual worms were genotyped at Hc-lgc-37, Hc-glc-5, Hc-avr-14 and Hc-dyf-7, and four microsatellite loci. High levels of polymorphism were identified at the first three candidate gene loci with remarkably little polymorphism at Hc-dyf-7. While some between-population comparisons of individual farms with and without long-term macrocyclic lactone use identified statistically significant differences in allele frequency and/or fixation index at the Hc-lgc-37, Hc-glc-5 or Hc-avr-14 loci, we found no consistent evidence of selection in other equivalent comparisons. While it is possible that different mechanisms are important in different populations or that resistance may be conferred by small changes at multiple loci, our findings suggest that these are unlikely to be major loci conferring macrocyclic lactone resistance on UK farms or suitable for diagnostic marker development. More powerful approaches, using genome-wide or whole genome sequencing, may be required to define macrocyclic lactone resistance loci in such genetically variable populations.